Aluminum fin material
The aluminum fin material with an amphoteric polyacrylamide resin and polyethylene glycol coating addresses icing and frost suppression, ensuring effective lubricity and hydrophilicity, enhancing heat exchanger performance.
Patent Information
- Application Number
- JP2021144231
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-03
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-09-03
AI Technical Summary
Existing heat exchanger fin materials face challenges in effectively suppressing icing and frost formation while maintaining hydrophilicity and lubricity, leading to ventilation resistance and reduced heat exchange efficiency.
An aluminum fin material with a coating layer containing an amphoteric polyacrylamide resin and polyethylene glycol, which can serve as an icing and frost suppressing film layer, optionally combined with a corrosion-resistant and hydrophilic film layer, to enhance lubricity and delay frost formation.
The coating layer effectively suppresses ice nucleation and frost formation, maintaining good lubricity and hydrophilicity, thereby improving the operational efficiency and durability of heat exchangers.
Smart Images

Figure 0007601731000003 
Figure 0007601731000004 
Figure 0007601731000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum fin material, and more particularly to an aluminum fin material that is suitable for use in heat exchangers of air conditioners and the like. [Background technology]
[0002] Heat exchangers are used in a variety of products, including room air conditioners, packaged air conditioners, freezer showcases, refrigerators, oil coolers, and radiators. Aluminum and aluminum alloys, which have excellent thermal conductivity, workability, and corrosion resistance, are generally used as materials for heat exchanger fins. Plate fin and plate and tube heat exchangers have a structure in which fin materials are arranged in parallel at close intervals.
[0003] When the surface temperature of the fin material of a heat exchanger falls below the dew point, condensed water adheres to it. If the surface of the fin material is not hydrophilic, the contact angle of the condensed water increases, causing it to splash around in the living environment, a phenomenon known as water splashing. When the condensed water combines and grows large, it forms a bridge between adjacent fin materials, blocking the ventilation passage between the fin materials and increasing ventilation resistance. For the purpose of preventing such water splashing and reducing ventilation resistance, for example, Patent Document 1 proposes a technique of applying and forming a hydrophilic coating on the surface of the fin material.
[0004] On the other hand, when the air conditioner is operated in heating mode, the surface temperature of the heat exchanger falls below the freezing point, and the condensed water on the surface of the fin material turns into frost or ice, resulting in frost formation. If the hydrophilicity is made too high, the frost formation becomes more likely to occur. If the fin material is blocked by the frost formation, the heat exchange efficiency of the heat exchanger is significantly reduced, and defrosting operation, etc. is required.
[0005] Therefore, various techniques for suppressing the formation of ice and frost on fin materials have been studied. For example, Patent Document 2 discloses that fluoroalkoxysilane with a critical surface tension of 20 dyn / cm or less is chemically adsorbed on the surface of the air-side heat transfer surface, and a coating having a structure in which CF3 groups are oriented on the outermost surface is formed, thereby imparting high water repellency and making the formation of frost less likely to occur. Patent Document 3 also discloses that a water-repellent coating is formed on the surface and the surface average roughness Ra is set to 20 μm or more, thereby reducing the area of water droplets (snow, ice) and reducing their adhesive force.
[0006] However, there are concerns that the water repellency may deteriorate over time, and that the durability may decrease due to a decrease in the strength of the water repellent coating when the average surface roughness Ra is increased. Therefore, Patent Document 4 discloses a heat exchanger having a first layer and a second layer located closer to the air than the first layer as a heat transfer part, the second layer being composed of a polymer layer having a plurality of polymer chains, and the roots of the main chains of adjacent polymer chains on the first layer side being bonded to each other by a metal oxide network structure. According to this, the polymer chains of the second layer can be bonded at high density in the direction perpendicular to the first layer, so that the hydrophilicity of the surface of the heat transfer part can be reliably improved, and even if condensed water occurs on the surface of the heat transfer part, the growth of frost can be sufficiently delayed. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 2520308 [Patent Document 2] Japanese Patent Application Publication No. 10-281690 [Patent Document 3] Japanese Patent Application Publication No. 9-228073 [Patent Document 4] JP 2019-158247 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, no specific study has been made on the suppression of icing and frost formation for the heat exchanger in Patent Document 4. In addition, it cannot necessarily be said that improved hydrophilicity improves the suppression of icing and frost formation, and a separate test on the suppression of icing and frost formation is necessary.
[0009] In response to this, the present inventors conducted extensive research into the anti-icing and anti-frosting coating layer and found that the use of an amphoteric polyacrylamide resin provides excellent anti-icing and anti-frosting effects. Further research suggested that it is difficult to achieve both lubricity, which corresponds to the workability of fin materials and is important from an industrial perspective, and anti-icing and anti-frosting properties.
[0010] Therefore, an object of the present invention is to provide an aluminum fin material having an icing / frost-preventing coating layer that has excellent icing / frost-preventing effect and also excellent lubricity. [Means for solving the problem]
[0011] The present invention relates to the following [1] to [3]. [1] An aluminum fin material having an aluminum plate and a coating layer formed on the surface of the aluminum plate, the coating layer comprising an anti-frost coating layer containing an amphoteric polyacrylamide resin and polyethylene glycol. [2] The aluminum fin material described in [1], further comprising a base treatment layer between the aluminum plate and the coating layer. [3] The aluminum fin material described in [1] or [2] above, wherein the coating layer is formed on both surfaces of the aluminum plate. Effect of the Invention
[0012] According to the present invention, the interaction between the condensed water adhering to the fin material surface and the frost-suppressing coating layer can suppress ice nucleation. As a result, the freezing of the condensed water is delayed, and frost formation on the surface is suitably suppressed. This frost-suppressing property and good lubricity can be achieved without interfering with each other's effects. Therefore, it is possible to provide an aluminum fin material that is advantageous for industrialization and suppresses frost formation. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the configuration of an aluminum fin material. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of the configuration of an aluminum fin material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the aluminum fin material according to the present invention will be described in detail. Note that the symbol "to" indicating a numerical range is used to mean that the numerical range includes the numerical ranges before and after the symbol as the lower and upper limits.
[0015] <Aluminum fin material> As shown in Fig. 1, the aluminum fin material 10 (hereinafter, sometimes simply referred to as "fin material") according to this embodiment has an aluminum plate 1 and a coating layer 2 formed on the surface of the aluminum plate 1. In addition, the coating layer 2 includes an icing / frosting suppression coating layer 2a containing an amphoteric polyacrylamide resin and polyethylene glycol.
[0016] The coating layer 2 may further include at least one of a corrosion-resistant coating layer and a hydrophilic coating layer. In this case, the position of the ice-frost-suppressing coating layer 2a is not particularly limited, but from the viewpoint of more suitably exhibiting the obtained ice-frost-suppressing property and lubricity, it is preferable that the ice-frost-suppressing coating layer 2a is the outermost layer, and it is more preferable that the corrosion-resistant coating layer 2b, the hydrophilic coating layer 2c, and the ice-frost-suppressing coating layer 2a are provided in this order from the aluminum plate 1 side, as shown in FIG.
[0017] In addition, in FIG. 2, the lubricating coating layer is not shown. This is because the frost-preventing coating layer can also provide good lubricity, and therefore there is no need to provide a separate lubricating coating layer.
[0018] In addition, the ice / frost-suppressing coating layer 2a may also function as the hydrophilic coating layer 2c. Details will be described later, but for example, by adjusting the content of polyethylene glycol in the ice / frost-suppressing coating layer 2a or by further including other additive components, the hydrophilic effect can be more suitably obtained, and an ice / frost-suppressing coating layer having the function of a hydrophilic coating layer can be obtained. frost It can be used as an inhibitory coating layer.
[0019] A base treatment layer may further be provided between the aluminum plate 1 and the coating layer 2. Furthermore, it is sufficient that the coating layer is formed on at least one surface of the aluminum plate 1, but in practice, it is preferable that the coating layer is formed on both surfaces of the aluminum plate 1. Furthermore, when the coating layers are formed on both surfaces of the aluminum plate 1, the coating layers do not need to be in the same form.
[0020] (Ice and frost prevention coating layer) The frost-suppressing coating layer 2a contains an amphoteric polyacrylamide resin and polyethylene glycol. The amphoteric polyacrylamide resin is an amphoteric polymer having a cationic group and an anionic group. Only one type of amphoteric polyacrylamide resin may be used, or two or more types of amphoteric polyacrylamide resins may be used.
[0021] Amphoteric polyacrylamide resins are composed of positively charged cationic groups and negatively charged anionic groups in the molecule.
[0022] The polar group portion of the cationic group of amphoteric polyacrylamide resin is -NR3 + Examples of the structure include a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt. Here, R can be a hydrogen atom, a linear or branched alkyl group having 1 to 5 carbon atoms, a salt, or the like.
[0023] Examples of the polar group portion in the anionic group of the amphoteric polyacrylamide resin include unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, unsaturated tricarboxylic acids, unsaturated tetracarboxylic acids, unsaturated sulfonic acids, unsaturated phosphonic acids, and salts thereof.
[0024] The method for producing the amphoteric polyacrylamide resin is not particularly limited, and a conventionally known method can be applied. For example, it can be obtained by a polymerization reaction of acrylamide with a cationic monomer having a cationic group and an anionic monomer having an anionic group. In addition, other monomers may be added as necessary. These polymerization reactions can be initiated, for example, by the addition of an initiator, and if necessary, a chain transfer agent, etc. may be added. Furthermore, the amphoteric polyacrylamide resin may be a commercially available product.
[0025] The anti-frost coating layer contains polyethylene glycol (PEG) in addition to the amphoteric polyacrylamide resin, and therefore has good lubricity, which contributes to processability. In this specification, the polyethylene glycol also includes modified polyethylene glycol, which is a modified compound of the polyethylene glycol. Modified polyethylene glycol is polyethylene glycol having one or more functional groups in its structure, which is obtained by, for example, introducing a urethane bond or substituting a terminal group with glycidyl ether. Among them, polyethylene glycol having no functional group is preferable from the viewpoint of improving hydrophilicity. The polyethylene glycol may be used alone or in combination of two or more kinds.
[0026] The anti-frost coating layer contains polyethylene glycol, and therefore can also enhance hydrophilicity. That is, in order to obtain good anti-frost properties, lubricity, and hydrophilicity, the content of polyethylene glycol per 100 parts by mass of amphoteric polyacrylamide resin is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more. The upper limit of the content of polyethylene glycol is preferably 100 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 25 parts by mass or less. When the icing / frost suppression coating layer has sufficient hydrophilicity, it can also function as the hydrophilic coating layer, so that it is not necessarily necessary to provide a separate hydrophilic coating layer.
[0027] The anti-frost coating layer may contain other optional components as long as the effects of the present invention are not impaired. Examples of the optional components include a crosslinking agent. By further containing a crosslinking agent, hydrophilicity can be further increased. Any known crosslinking agent can be used, and examples of such crosslinking agents include crosslinkers containing an oxazoline group, an oxiranyl group (1,2-epoxy structure), an oxetanyl group (1,3-epoxy structure), an isocyanate group, a blocked isocyanate group, etc. Among these, an oxazoline group or an oxiranyl group is more preferred.
[0028] The anti-frost coating layer preferably further contains, as an optional component, a surfactant, for example, in order to further enhance hydrophilicity. By containing a surfactant, both processability and hydrophilicity can be more preferably achieved. This is believed to be due to the exposing action of the surfactant.
[0029] The surfactant may be any of anionic, cationic and nonionic types, but nonionic surfactants are preferred from the viewpoint of ease of dispersion in the anti-frost coating layer.
[0030] Examples of the anionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkyl ether phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl sulfosuccinates, and polyoxyethylene polyoxypropylene block copolymers.
[0031] Examples of nonionic surfactants include ethylenediamine polyoxypropylene-polyoxyethylene condensates, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene block polymers, polyoxyethylene sorbitan monostearate, and the like.
[0032] The frost-preventing coating layer may further contain, as an optional component, an inorganic material, for example, from the viewpoint of enhancing hydrophilicity. Examples of the inorganic material include compounds containing silicon and compounds containing titanium, such as colloidal silica, sodium silicate, silicone oligomer, silane coupling agent, titanium alkoxide, and titanium oxide.
[0033] The icing / frost-suppressing coating layer can be formed by applying a paint composition containing an amphoteric polyacrylamide resin and polyethylene glycol onto an aluminum plate or layer on which the icing / frost-suppressing coating layer is to be formed, drying the composition, and solidifying the composition by baking or the like. The content of the amphoteric polyacrylamide resin in the frost-preventing coating layer is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, in terms of solid content ratio, and is preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 90% by mass or less.
[0034] The content of polyethylene glycol in the frost-preventing coating layer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, in terms of solid content ratio, and is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.
[0035] When the frost-preventing coating layer contains a crosslinking agent, the content of the crosslinking agent relative to 100 parts by mass of the amphoteric polyacrylamide resin is preferably 1 part by mass or more, more preferably 3 parts by mass or more, in terms of solid content ratio, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less.
[0036] When the frost-preventing coating layer contains a surfactant, the content of the surfactant relative to 100 parts by mass of the amphoteric polyacrylamide resin is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, in terms of solid content ratio.
[0037] When the anti-frost coating layer contains an inorganic material, the content of the inorganic material relative to 100 parts by mass of the amphoteric polyacrylamide resin is preferably 1 part by mass or more, more preferably 5 parts by mass or more, in terms of solid content ratio, and is preferably 35 parts by mass or less, more preferably 30 parts by mass or less.
[0038] The amount of the anti-icing / frosting coating layer is 0.1 mg / dm2 in order to obtain sufficient anti-icing / frosting effect and lubricity. 2 More than 0.5 mg / dm 2 More preferably, 1 mg / dm 2 The upper limit is not particularly limited, but the coating amount of the anti-frost coating layer is preferably 50 mg / dm 2 Less than 30 mg / dm 2 The following is more preferred:
[0039] The anti-frost coating layer may contain other optional components within the scope of the present invention, such as various water-based solvents and paint additives for improving the paintability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, anti-fungal agents, etc. These paint additives may be contained alone or in combination of two or more.
[0040] The thickness of the anti-icing / frosting coating layer is not particularly limited, but the density of the anti-icing / frosting coating layer is preferably 1 g / cm 3 Assuming that, in order to obtain good frost suppression properties and lubricity, the thickness is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. The upper limit is not particularly limited, but is preferably 5 μm or less, and more preferably 3 μm or less. The thickness of the anti-icing / frosting coating layer can be adjusted by the concentration of the coating composition used to form the anti-icing / frosting coating layer, the selection of the bar coater number, and the like.
[0041] (Aluminum plate) The aluminum plate is a concept that includes a plate made of aluminum and a plate made of an aluminum alloy, and an aluminum plate that has been conventionally used for aluminum fin materials can be used. As the aluminum plate, 1000 series aluminum as specified in JIS H 4000:2014 is preferable because of its excellent thermal conductivity and workability. More specifically, aluminum alloy numbers 1050, 1070, and 1200 are more preferable as the aluminum plate. However, the above description does not exclude the use of 2000 series to 9000 series aluminum alloys or other aluminum plates as the aluminum plate.
[0042] The aluminum plate is made to have a desired thickness depending on the application and specifications of the fin material. For fin materials for heat exchangers, the thickness is preferably 0.08 mm or more, more preferably 0.1 mm or more, from the viewpoint of the strength of the fin. On the other hand, the thickness is preferably 0.3 mm or less, more preferably 0.2 mm or less, from the viewpoint of the workability into fins and the heat exchange efficiency.
[0043] (Corrosion-resistant coating layer) The corrosion-resistant coating layer may be formed on the aluminum plate mainly for the purpose of enhancing the corrosion resistance of the aluminum plate, and preferably contains a hydrophobic resin. In the case where a base treatment layer is formed on the surface of the aluminum plate, the corrosion-resistant coating layer is formed on the base treatment layer. In addition, considering that the anti-icing / frosting coating layer is preferably the outermost layer, it is preferable that the corrosion-resistant coating layer is formed on the aluminum plate or the base treatment layer. The corrosion-resistant coating layer can be formed, for example, by applying a coating composition containing a hydrophobic resin onto an aluminum plate or layer, drying and baking the coating.
[0044] The corrosion-resistant coating layer makes it difficult for moisture such as condensation water, oxygen, chloride ions and other ionic species to penetrate the aluminum plate, thereby suppressing corrosion of the aluminum plate and the production of odorous aluminum oxides.
[0045] The hydrophobic resin in the corrosion-resistant coating layer may be a conventionally known resin, such as polyester, polyolefin, melamine, epoxy, urethane, or acrylic resin, or a mixture of two or more of these resins.
[0046] In addition to the above, the corrosion-resistant coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of optional components include various water-based solvents and paint additives for improving the paintability, workability, and physical properties of the coating. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.
[0047] The amount of the corrosion-resistant coating layer is not particularly limited, but from the viewpoint of imparting sufficient corrosion resistance to the aluminum plate, it is preferably 0.5 mg / dm 2 More than 2 mg / dm is preferable. 2 On the other hand, from the viewpoint of suppressing the decrease in the heat exchange efficiency of the fin, the coating amount of the corrosion-resistant coating layer is preferably 150 mg / dm 2 Less than 50 mg / dm 2 The following is more preferred:
[0048] The thickness of the corrosion-resistant coating layer is preferably 0.05 μm or more from the viewpoint of obtaining good corrosion resistance, and is preferably 15 μm or less from the viewpoints of good film-forming properties, reduced defects such as cracks, low heat transfer resistance of the corrosion-resistant coating layer, and good heat exchange efficiency of the fin. The thickness of the corrosion-resistant film layer and the amount of hydrophobic resin applied can be adjusted by the concentration of the coating composition used to form the corrosion-resistant film layer and the selection of the bar coater number.
[0049] (Hydrophilic film layer) The hydrophilic coating layer is a coating layer that imparts hydrophilicity to the surface of the fin material, and contains a conventionally known hydrophilic resin. The hydrophilic resin may contain one type of resin as long as it has a hydrophilic group, and may contain two or more types of resin. Examples of hydrophilic groups include hydroxyl groups, carboxyl groups, sulfonic acid groups, polyether groups, and the like. However, if the anti-frost coating layer has sufficient hydrophilicity and can also function as a hydrophilic coating layer, the hydrophilic coating layer may not be necessary. Even if the anti-frost coating layer has sufficient hydrophilicity, a hydrophilic coating layer may be provided for the purpose of further hydrophilicity or durability of hydrophilicity.
[0050] Examples of those having a hydroxyl group include polyethylene glycol (PEG) and polyvinyl alcohol (PVA). Examples of those having a carboxyl group include polyacrylic acid (PAA). Examples of those having a hydroxyl group and a carboxyl group include carboxymethyl cellulose (CMC). Examples of those having a sulfonic acid group include sulfoethyl acrylate. Examples of those having a polyether group include polyethylene glycol (PEG) and modified compounds thereof.
[0051] Among these, from the viewpoint of more suitably expressing the desired hydrophilicity even when an icing / frost-suppressing coating layer is formed on the surface of the hydrophilic coating layer, the hydrophilic resin is preferably one containing a sulfonic acid group or a polyether group, i.e., one containing an ether bond, more preferably one containing a sulfonic acid group and an ether bond, and particularly preferably an acrylic acid resin containing a sulfonic acid group and an ether bond.
[0052] The acrylic acid resin containing sulfonic acid and an ether bond is an acrylic acid resin containing an unsaturated double bond group and a sulfonic acid group, and examples thereof include polyvinyl ether-sulfonic acid acrylic copolymer, benzyl ether-sulfonic acid acrylic copolymer, etc. However, the acrylic acid resin containing sulfonic acid and an ether bond is not limited to these.
[0053] In addition to the above, the hydrophilic resin may be a copolymer of two or more monomers having a hydrophilic group. For example, a copolymer of acrylic acid and sulfoethyl acrylate may be used. The copolymer may be an alternating copolymer, a block copolymer, a graft copolymer, a random copolymer, or the like, and the arrangement of the monomers is not particularly limited.
[0054] It is preferable that the hydrophilic coating layer further contains a surfactant in addition to the hydrophilic resin. This allows the effect of the coating layer and better hydrophilicity to be achieved even if an anti-frost coating layer is formed on the hydrophilic coating layer. This is believed to be due to the exposing action of the surfactant.
[0055] The surfactant may be any of anionic, cationic and nonionic types, but nonionic surfactants are preferred from the viewpoint of ease of dispersion in the hydrophilic coating layer.
[0056] Examples of nonionic surfactants include ethylenediamine polyoxypropylene-polyoxyethylene condensates, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene block polymers, polyoxyethylene sorbitan monostearate, and the like.
[0057] The hydrophilic coating layer can be formed by applying a coating composition containing a hydrophilic resin onto an aluminum plate, a base treatment layer, or a corrosion-resistant coating layer, drying it, and solidifying it by baking, etc. In addition, considering that the icing / frost-suppressing coating layer is preferably the outermost layer, it is preferable that the hydrophilic coating layer is formed on the aluminum plate, a base treatment layer, or a corrosion-resistant coating layer.
[0058] The amount of the hydrophilic coating is 0.1 mg / dm2 to obtain sufficient hydrophilicity. 2 More than 0.5 mg / dm 2 More preferably, 1 mg / dm 2 More preferably, the amount of the hydrophilic coating layer is 50 mg / dm2 or more. In order to prevent the hydrophilic resin from eluting when the surface of the fin material becomes wet with water, thereby preventing the effect of the anti-icing and frosting coating layer from being impaired, the amount of the hydrophilic coating layer is 50 mg / dm2 or more. 2 Less than 30 mg / dm 2 Less than 10 mg / dm is more preferable. 2 The following is even more preferred:
[0059] In addition to the hydrophilic resin and surfactant, the hydrophilic coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of the optional components include various water-based solvents and paint additives for improving the coatability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.
[0060] The thickness of the hydrophilic coating layer is not particularly limited, but the density of the hydrophilic coating layer is preferably 1 g / cm 3 Assuming this, in order to obtain good hydrophilicity, the thickness is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. The upper limit is not particularly limited, but is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. The thickness of the hydrophilic coating layer can be adjusted by the concentration of the coating composition used to form the hydrophilic coating layer, the selection of the bar coater number, and the like.
[0061] The total thickness of the coating layers of the fin material is preferably 5 μm or less from the viewpoint of suppressing a decrease in the heat exchange efficiency of the fin material. The coating layers include an anti-frost coating layer, and an optional corrosion-resistant coating layer and a hydrophilic coating layer.
[0062] (Base treatment layer) A primer layer may optionally be provided on the aluminum plate. By providing a base treatment layer, the corrosion resistance of the aluminum plate can be increased, and when a corrosion-resistant coating layer is further provided, the adhesion between the aluminum plate and the corrosion-resistant coating layer can be increased.
[0063] The undercoat treatment layer may be any layer that can impart corrosion resistance to the aluminum plate, and may be any layer known in the art, such as a layer made of an inorganic oxide or an inorganic-organic composite compound. As the inorganic material constituting the inorganic oxide or inorganic-organic composite compound, chromium (Cr), zirconium (Zr) or titanium (Ti) is preferred as the main component.
[0064] The layer made of an inorganic oxide that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic acid phosphate treatment, etc. However, the type of inorganic oxide is not limited to those formed by these treatments.
[0065] The layer made of an inorganic-organic composite compound that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to coating-type chromate treatment, coating-type zirconium treatment, etc. Specific examples of such inorganic-organic composite compounds include, for example, acrylic-zirconium composites.
[0066] The thickness of the undercoat treatment layer is not particularly limited and may be set appropriately, but the amount of adhesion per unit area is preferably 1 to 100 mg / m in terms of metal (Cr, Zr, Ti). 2 The thickness of the film is preferably 1 to 100 nm. The deposition amount and film thickness of the undercoat treatment layer can be adjusted by adjusting the concentration of the chemical conversion treatment solution used in forming the undercoat treatment layer and the film formation treatment time.
[0067] Before forming the primer layer, the surface of the aluminum plate may be degreased in advance using an alkaline degreasing solution, which improves the reactivity of the primer treatment and also improves the adhesion of the formed primer layer.
[0068] (Characteristics of aluminum fin material) The aluminum fin material according to this embodiment can suppress ice nucleation even when condensation water adheres to its surface due to the interaction between the condensation water and the anti-frost coating layer. As a result, the freezing of the condensation water is delayed, and the formation of frost on the surface of the fin material can be suppressed. In addition, good lubricity can be achieved without impairing the anti-frost property.
[0069] The frost suppression effect of the fin material can be evaluated by the following method. A copper plate equipped with a refrigerant flow path, a Peltier element, and an air flow path is placed in the upper part of the inside of an acrylic cylinder, and the device is placed in an environment of a temperature of 10°C and a relative humidity of 55%. A test material formed by cutting a fin material to, for example, 35 mm x 57 mm is placed on the copper plate at a position in contact with the air inside the cylinder. Then, air is blown into the cylinder at a speed of 1.5 m / s. After the above process, the copper plate is cooled while continuing to blow air into the tube at the same air speed, the surface temperature is set to -7.5°C, and condensation water is intentionally formed on the surface of the test material. A digital microscope is placed on the side of the test material where the condensation water adheres, and the state of condensation water and frost on the surface of the test material is observed. The time from the start of cooling to the start of frost formation is measured as the "frost formation delay time" and the frost formation suppression effect is evaluated. The frost formation delay time according to the above method is preferably 3 minutes or more, more preferably 5 minutes or more. There is no particular upper limit, and the longer the better.
[0070] The lubricating effect of the fin material can be evaluated by the following method. The friction coefficient is measured on the surface of the aluminum fin material using a Bowden tester under conditions of a load of 200g and 25°C, and the lubricity is evaluated. The coefficient of friction obtained by the above method is preferably 0.15 or less, more preferably 0.12 or less. Although there is no particular lower limit, it is usually 0.05 or more.
[0071] When using a fin material in a heat exchanger, hydrophilicity is also an important parameter. Therefore, the hydrophilicity of the fin material can be evaluated by the contact angle when pure water is dropped on the surface of the fin material. Specifically, about 2 μL of pure water is dropped onto the surface of the fin material at room temperature, and the contact angle of the droplet (pure water) is measured using a contact angle measuring device. The contact angle of the droplet (pure water) is preferably 30° or less, more preferably 20° or less. The lower limit is not particularly limited, but is usually 5° or more.
[0072] <Method of manufacturing aluminum fin material> An example of a manufacturing method for the aluminum fin material according to this embodiment will be described, but the present invention is not limited to this embodiment, and other manufacturing methods can also be used as long as they do not interfere with the effects of this embodiment. The following example describes a case where a base treatment layer, a corrosion-resistant film layer, and an anti-icing / frosting film layer are formed in this order on the surface of an aluminum plate, but the formation of the base treatment layer and the corrosion-resistant film layer is optional. A hydrophilic film layer may also be formed. In this case, the hydrophilic film layer can be formed by a conventionally known method. The anti-icing / frosting film layer may be formed at any position, but it is preferable to form it on the outermost layer.
[0073] A base treatment layer is formed on the surface of an aluminum plate by a known method, and a corrosion-resistant coating layer is formed on the surface by a known method. Next, a coating composition containing an amphoteric polyacrylamide resin and polyethylene glycol is applied onto the corrosion-resistant coating layer, dried, and baked to form an anti-icing / frosting coating layer. The coating composition containing the amphoteric polyacrylamide resin and polyethylene glycol may contain other components such as a crosslinking agent, a surfactant, and an inorganic material.
[0074] The solvent of the coating composition containing an amphoteric polyacrylic resin and polyethylene glycol is not particularly limited, and examples thereof include water, alcohol, aliphatic ketones, etc. Among these, water and alcohol are preferred, and as the alcohol, butanol, ethanol, etc. are preferred. The solvent may be used alone or in combination of two or more. For example, in the case of a mixed solvent of water and alcohol, it is preferable from the viewpoint of coatability onto a substrate that the amount of alcohol is 1 to 20 parts by mass per 100 parts by mass of water.
[0075] The solid content concentration in the coating composition containing the amphoteric polyacrylic resin and polyethylene glycol is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 5.0% by mass or more, from the viewpoint of coatability on a substrate. The solid content concentration is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, from the viewpoint of coatability on a substrate.
[0076] The thickness of the coating film when the coating composition containing the amphoteric polyacrylic resin and polyethylene glycol is applied is preferably 1 μm or more, more preferably 5 μm or more, from the viewpoint of coatability to the substrate. Also, the thickness of the coating film is preferably 40 μm or less, more preferably 20 μm or less, from the viewpoint of volatility of the solvent. Note that the thickness here is the thickness before drying, and when the coating composition is applied using a bar coater, for example, it can be adjusted by selecting the bar coater number.
[0077] The application of the corrosion-resistant coating layer, the hydrophilic coating layer, and the anti-icing / frosting coating layer is carried out by a bar coater, a roll coating method, etc. In particular, when the aluminum plate is in a coil shape, it is preferable in terms of productivity to use a roll coating device or the like to continuously carry out degreasing, painting, heating, winding, etc. In addition, the baking temperatures of the corrosion-resistant coating layer, the hydrophilic coating layer, and the anti-icing / frosting coating layer may be set according to the components of the resins, etc., respectively used, and are preferably in the range of, for example, 120 to 270°C. EXAMPLES
[0078] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and can be practiced with modifications within the scope of the invention, all of which are included in the technical scope of the present invention.
[0079] Example 1 The aluminum plate used was an alloy number 1070 aluminum plate specified in JIS H 4000:2014 with a thickness of 0.095 mm, and a phosphate chromate treatment was applied to the aluminum plate as a base treatment layer. Next, a coating composition containing amphoteric polyacrylamide resin (T-MP183, manufactured by Seiko PMC Corporation) and polyethylene glycol (PEG20000, manufactured by Sanyo Chemical Industries, Ltd.) was prepared using water as a solvent, and applied to the surface of the aluminum plate that had been subjected to a primer treatment using a bar coater. The coating was then dried and baked to form an anti-icing and frosting coating layer, thereby obtaining an aluminum fin material. The solid content ratio of the amphoteric polyacrylamide resin and polyethylene glycol is as shown in Table 1. The coating amount of the anti-icing and frosting coating layer was 3.7 mg / dm 2 It was.
[0080] Example 2 In the same manner as in Example 1, a base treatment layer was formed on an aluminum plate, and then a coating composition containing a modified urethane resin was applied with a bar coater, dried, and baked to form a corrosion-resistant coating layer. The coating amount of the corrosion-resistant coating layer was 10 mg / dm 2 It was. Next, a coating having a coating amount of 3.7 mg / dm2 was applied to the surface of the corrosion-resistant coating layer in the same manner as in Example 1. 2 An anti-icing / frosting coating layer was formed on the aluminum fin material to obtain an aluminum fin material.
[0081] Comparative Example 1 An aluminum fin material was obtained in the same manner as in Example 1, except that the coating composition used for the anti-icing and frosting coating layer contained only the same amphoteric polyacrylamide resin as in Example 1 and did not contain polyethylene glycol. The coating amount of the anti-icing and frosting coating layer was 3.1 mg / dm 2 It was.
[0082] Comparative Example 2 A coating composition containing polyethylene glycol was further applied to the surface of the anti-frost coating layer obtained in Comparative Example 1, and baked to form a functional layer, thereby obtaining an aluminum fin material. The coating amount of the functional layer made of polyethylene glycol was 0.6 mg / dm 2 It was.
[0083] Comparative Example 3 As in Example 1, a base treatment layer was formed on an aluminum plate, and then a coating composition containing silica was applied and baked to form a functional layer, thereby obtaining an aluminum fin material. The coating amount of the functional layer made of silica was 200 mg / dm 2 It was.
[0084] Comparative Example 4 The coating composition used for the anti-icing and frosting coating layer was a coating composition containing an amphoteric polyacrylamide resin and an oxazoline crosslinking agent (Epocross (registered trademark) WS700, manufactured by Nippon Shokubai Co., Ltd.), and the solid content composition ratio was set as shown in Table 1. An aluminum fin material was obtained in the same manner as in Example 1. The coating amount of the anti-icing and frosting coating layer was 3.2 mg / dm 2 It was.
[0085] Comparative Example 5 An aluminum fin material was obtained in the same manner as in Example 1, except that the coating composition used for the anti-icing and frosting coating layer was a coating composition containing an amphoteric polyacrylamide resin and ammonium zirconyl carbonate, and the solid content ratios thereof were as shown in Table 1. The coating amount of the anti-icing and frosting coating layer was 3.2 mg / dm 2 It was.
[0086] Comparative Example 6 An aluminum fin material was obtained in the same manner as in Example 1, except that the coating composition used for the anti-icing / frosting coating layer was a coating composition containing an amphoteric polyacrylamide resin and a surfactant A, and the solid content ratios thereof were as shown in Table 1. The coating amount of the anti-icing / frosting coating layer was 3.2 mg / dm 2 It was.
[0087] Comparative Example 7 An aluminum fin material was obtained in the same manner as in Example 1, except that the coating composition used for the anti-icing / frosting coating layer was a coating composition containing an amphoteric polyacrylamide resin and surfactant B, and the solid content ratios thereof were as shown in Table 1. The coating amount of the anti-icing / frosting coating layer was 3.2 mg / dm 2 It was.
[0088] Comparative Example 8 The coating composition used for the anti-icing and frosting coating layer was a coating composition containing an amphoteric polyacrylamide resin and carboxymethylcellulose (Cerogen PR, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and the solid content ratios thereof were as shown in Table 1. An aluminum fin material was obtained in the same manner as in Example 1. The coating amount of the anti-icing and frosting coating layer was 3.2 mg / dm 2 It was.
[0089] Comparative Example 9 An aluminum fin material was obtained in the same manner as in Example 1, except that the coating composition used for the anti-icing / frosting coating layer was a coating composition containing an amphoteric polyacrylamide resin and a hydrophilic resin, and the solid content ratio thereof was set as shown in Table 1. The coating amount of the anti-icing / frosting coating layer was 3.7 mg / dm 2 It was.
[0090] Comparative Example 10 As in Example 2, a base treatment layer was formed on an aluminum plate, and a coating composition containing a modified urethane resin was applied with a bar coater and baked to form a corrosion-resistant coating layer. The coating amount of the corrosion-resistant coating layer was 10 mg / dm 2 It was. Next, a coating composition containing an amphoteric polyacrylamide resin but not containing polyethylene glycol was applied to the surface of the corrosion-resistant coating layer in the same manner as in Comparative Example 1, so that the coating amount was 3.1 mg / dm 2 An anti-icing / frosting coating layer was formed on the aluminum fin material to obtain an aluminum fin material.
[0091] (Evaluation: frost suppression) A copper plate equipped with a refrigerant flow path, a Peltier element, and an air flow path was placed in the upper part of the inside of an acrylic cylinder, and the device was placed in an environment of a temperature of 10°C and a relative humidity of 55%. A test material formed by cutting an aluminum fin material to 35 mm x 57 mm was placed on the copper plate at a position in contact with the air inside the cylinder. Then, air was blown into the cylinder at a speed of 1.5 m / s. After the above process, the copper plate was cooled while continuing to blow air into the tube at the same air speed, the surface temperature was set to -7.5°C, and condensation water was intentionally allowed to adhere to the surface of the fin material. A digital microscope was placed on the side of the test material where the condensation water was attached, and the state of the condensation water and frost on the surface of the test material was observed. The time from the start of cooling to the start of frost formation was measured as the "frost formation delay time" and the frost formation suppression ability was evaluated. The evaluation criteria are as follows, and the results are shown in "Ice and frost suppression" in Table 2. In Table 2, "-" indicates that the measurement was not performed. A Good (passed): Icing delay time is 3 minutes or more B Bad (failed): Frost formation delay time is less than 3 minutes
[0092] (Evaluation: Lubricity) The friction coefficient was measured on the surface of the aluminum fin material using a Bowden tester (TS502, manufactured by Kyowa Interface Science Co., Ltd.) under conditions of a load of 200 g and 25°C, and lubricity was evaluated. The evaluation criteria are as follows, and the results are shown in "Lubricity" in Table 2. In Table 2, "-" means that the measurement was not performed. A Good (passed): Friction coefficient is 0.15 or less B Bad (failed): Friction coefficient is more than 0.15
[0093] (Evaluation: Hydrophilic) At room temperature, about 2 μL of pure water was dropped onto the surface of the aluminum fin material, and the contact angle of the droplet (pure water) was measured using a contact angle measuring device (Kyowa Interface Science Co., Ltd., CA-05 model). The evaluation criteria are as follows, and the results are shown in "hydrophilicity" in Table 2. In Table 2, "-" indicates that the measurement was not performed. A Good (passed): Contact angle is 30° or less B Bad (failed): Contact angle is more than 30°
[0094] [Table 1]
[0095] [Table 2]
[0096] From the above results, it was found that the aluminum fin material provided with the anti-frost coating layer containing the amphoteric polyacrylamide resin and polyethylene glycol can achieve very good anti-frost properties and lubricity. In addition, the hydrophilicity was also very good.
[0097] On the other hand, when the anti-frost coating layer did not contain polyethylene glycol as in Comparative Example 1, good anti-frost properties were obtained, but the lubricity was poor. Also, when the anti-frost coating layer made of amphoteric polyacrylamide resin and the coating layer made of polyethylene glycol were separately provided as in Comparative Example 2, good lubricity was obtained, but the anti-frost properties were poor. controlThus, it was found that providing an anti-icing / frosting coating layer containing both an amphoteric polyacrylamide resin and polyethylene glycol is essential to achieve both an anti-icing / frosting effect and good lubricity. [Explanation of symbols]
[0098] 1 Aluminum plate 2. Coating layer 2a Anti-icing film layer 2b Corrosion-resistant coating layer 2c Hydrophilic film layer 10 Aluminum fin material
Claims
1. The coating layer includes an aluminum plate and a coating layer formed on a surface of the aluminum plate. The coating layer comprises an anti-frost coating layer containing an amphoteric polyacrylamide resin and polyethylene glycol, The content of the amphoteric polyacrylamide resin in the frost-suppressing coating layer is 50% by mass or more and 99% by mass or less in terms of solid content ratio, The content of the polyethylene glycol in the frost-preventing coating layer is 1% by mass or more and 50% by mass or less in terms of solid content ratio.
2. The aluminum fin material according to claim 1 , further comprising a base treatment layer between the aluminum plate and the coating layer.
3. The aluminum fin material according to claim 1 or 2, wherein the coating layer is formed on both surfaces of the aluminum plate.
Citation Information
Patent Citations
Water-repelelnt member and method for preventing coating of snow and ice using the member
JP1997228073A
Air conditioner, heat exchanger and its production
JP1998281690A
Resin composition exhibiting high performance in inhibition of ice and frost formation, and laminated metal plate on which ice / frost-formation inhibition layer is formed
JP2011089112A
Hydrophilic treatment agent composition
JP2012025820A
Surface treatment agent, manufacturing method of coated film and metal material with coated film
JP2017043744A
